Evolution of agrarian policy and production performances of Serbian agriculture - Zekić, Stanislav; Gajić, Milivoj; Koviljko, Lovre; Kresoja, Marinko; Tošin, Miloš (Economics of Agriculture, 2010)
From the middle of the previous century until today, an analysis of the evolution of the agrarian policy in Serbia shows that various models of agricultural policy are influenced by ruling political and ideological motives. The period of socialist agriculture, which has since been followed by transitional changes lasting to the present day and is now reflected in efforts towards joining the EU, has, to a great extent, determined the developmental characteristics of Serbian agriculture. In that context, production performances of Serbian agriculture have been discussed considering agricultural production dynamics and the level and motion of partial agricultural productivity in comparison with European Union countries.